WORK-LIFE CONFLICT AND SEXUAL HARASSMENT IMPACT TOWARDS EMPLOYEE TURNOVER INTENTIONS AT GMIM KALOORAN AMURANG HOSPITAL - Kembuan, Argeiny; Kalangi, Josep B.; Arie, Fitty Valdi (Universitas Sam Ratulangi, 2021)
Employees are the most important assets of the organization that is why organizations always try to avoid losing their employees because employees are the key performers to obtain the organization's expected success. Nowadays, the big problem of the organization is to maintain the employee from having the intention to leave or to turnover, especially the employee who has a quality of human resources. This research aims to know the work-life conflict and sexual harassment impact towards employee turnover intentions at GMIM Kalooran Amurang hospital with a quantitative approach. The binary logistic regression method was used to analyze the impact of work-life conflict and sexual harassment on employee turnover intentions. The data collection method in this research used secondary data and primary data, where the primary data was obtained from the questionnaires of the 53 samples of employees in GMIM Kalooran Amurang Hospital. The results of this research suggested that work-life conflict does not have an impact on employee turnover intentions at GMIM Kalooran Amurang Hospital partially, sexual harassment have an impact on employee turnover intentions at GMIM Kalooran Amurang Hospital partially, and work-life conflict and sexual harassment have an impact towards employee turnover intentions at GMIM Kalooran Amurang Hospital simultaneously.